An update on the status of nerve monitoring for thyroid/parathyroid surgery. Issue 1 (January 2017) - Lin, Ho-Sheng; Terris, David J.
Abstract : Purpose of review: Recurrent laryngeal nerve (RLN) injury is one of the most common and serious complications associated with thyroid and parathyroid surgery. Although routine visual identification of the RLN is considered the current standard of care, the role of intraoperative neuromonitoring (IONM) of the RLN is more controversial. Recent findings: Despite initial enthusiasm that IONM might substantially reduce the rate of RLN injury, most studies failed to show a significant difference in the rate of RLN injury when the use of IONM was compared with visualization of the RLN alone. However, a small number of investigators have reported statistically significant differences in the rates of nerve injury when IONM is used to augment visualization alone, particularly in certain high-risk situations. Despite a lack of conclusive data showing benefit, the use of IONM as an adjunct to visual identification of the RLN has gained increasing acceptance among surgeons. IONM remains an excellent tool to help verify the identity of the RLN, confirm its functional integrity, and pinpoint the site of nerve injury in the event of dysfunction. Summary: The utility of IONM in reducing the rate of RLN injury is largely unproven and remains controversial. However, the use of IONM may be helpful in certain high-risk cases. Promising new technology, such as vagal nerve monitoring, may allow more real-time monitoring of the functional integrity of the RLN and allow the surgeon to react in a timely manner to evolving dysfunction in order to abort maneuvers that may risk definitive injury.